Assessment of Capital Requirements of Commercial Banks in Malaysia - Ro'ziyevich, Dehkanov Mirvohid (2010)
We analyze the determinants of Capital Adequacy Ratio (CAR) using a sample of twenty local and foreign commercial banks operating in Malaysia based on Base1 II Accord for the period of 5 years, from 2005 to 2009. The main objective of this study is to identify the problem of complying with Base1 II Accord, to find out the level of CAR of commercial banks and to identify the component of risk consists of credit risk, market risk and operational risk in commercial banks. This study has chosen multiple regression analysis to identify the determinants of capital requirements in Malaysian foreign and domestic commercial banks based on Basel II Accord for the period of 2005-2009. The dependent variable is CAR, where as the independent variables are credit risk (CRR), market risk (MRR), operational risk (MRR), LogSize, loan loss provision (LLP). The study has found that all Malaysian banks were committed by a minimum 8% capital adequacy ratio while most of them had higher than 8% ratio. By doing this research we have found that both local and foreign commercial banks showed more confidence and adequate. Both existing local and foreign banks are affecting financial services quality in Malaysia, because all banks offer better and low cost banking services for customer during cut-throat competition.